Розвиток рухової активності студенток у процесі занять скандинавською ходьбою = Development physical activity of students in the training process nordic walking - Olga Kasarda (Kazimierz Wielki University, 2015)
Kasarda O. Розвиток рухової активності студенток у процесі занять скандинавською ходьбою = Development physical activity of students in the training process nordic walking. Journal of Education, Health and Sport. 2015;5(6):519-532. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44702 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A519-532 https://pbn.nauka.gov.pl/works/693748 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.04.2015. Revised 05.05.2015. Accepted: 26.06.2015.   розвиток рухової активності студенток у процесі занять скандинавською ходьбою DEVELOPMENT physical activity of students in the training process Nordic Walking   Касарда О. Kasarda O.   Луцький національний технічний університет Lutsk National Technical University   Анотація Розроблено й обґрунтовано програму розвитку рухової активності студенток вищих навчальних закладів у процесі занять скандинавською ходьбою. На першому етапі студентки вивчали техніку скандинавської ходьби дотримуючись послідовності та доступності формування рухових умінь і навичок. Зміст занять спрямовувався на поступове підвищення функціональних можливостей серцево-судинної і дихальної систем організму дівчат. На другому етапі проводились систематичні заняття скандинавською ходьбою відповідно до розробленого змісту і дозування навантажень. Основні завдання цього етапу полягали у розвитку фізичних якостей, підвищенні захисних сил і опірності організму до несприятливих факторів зовнішнього середовища. Третій етап полягав у продовженні систематичних занять скандинавською ходьбою, підтримці досягнутого рівня функціонування організму   Ключові слова: скандинавська ходьба, рухова активність, програмування навантажень, студенти, позааудиторні заняття.   Abstract In the thesis is developed and substantiated the program of development of motor activity of students of higher educational institutions in the process of Nordic walking is developed and substantiated. In the first stage, students studied the technique of Nordic walking observing the consistency and availability of forming of motive abilities and skills. The content of the lessons was focused on gradual increase of the functional possibilities of the cardiovascular and respiratory systems of the girls' organism. In the second stage there was systematic Nordic walking according to the developed content and load dosage. The main task of this phase was to develop physical qualities, improve the body's defensive forces and the body's resistance to adverse environmental factors. The third stage consisted in the continuation of systematic Nordic walking, maintaining the achieved level of functioning of the body.   Keywords: Nordic walking, physical activity, programming of loads, students, extracurricular classes.